Success against the odds: A case study - Ahmadbayli, Aydan (2015)
The purpose of this dissertation is to examine the leadership behaviours and practices necessary for school ‘turnaround’. The research was conducted by taking a multi perspective approach within a qualitative research study to explore the case of a UK based school facing ‘special measures’ and in disadvantaged circumstances. Research methods employed include a documentary study and semi-structured interviews with six members of staff. The results indicated that effective turnaround leaders employ a complex set of behaviours and practices.